Recruitment and Selection Practices adopted by SMEs in Microfinance Firms in the Accra Metropolitan Area of Ghana - Nyarko, Cynthia Oduro (Advances in Social Sciences Research Journal, 2016)
This study sought to investigate the Recruitment and Selection practices among small and medium businesses using the microfinance sector of the Ghanaian economy. A cross-sectional survey design was used for the study and data were obtained through questionnaire from 40 managers of small and medium size microfinance firms in the Accra Metropolitan Area of the Greater Accra Region of Ghana. Descriptive statistics with tables and frequencies were used for the analysis. The study found out that managers mainly recruit by word-of-mouth. They did not use sophisticated recruitment strategies, and selection was mainly done through practical tests and interviews among others. Their candidates normally come from the recommendation of friends and relations. In a nutshell, the microfinance institutions use recruitment and selection practices that are cost effective and less time consuming instead of the available sophisticated practices.